Craniofacial fibrosarcoma: a case report (Tanzania Medical Journal, 2010)
Fibrosarcoma (FS) is a malignant proliferation of fibroblasts. Malignancies of fibroblasts are decidedly rare in the oral and oropharyngeal region, but FS is, nevertheless, the commonest mesenchymal cancer of the region, representing more than half of all sarcomas .This article reports a case of a seventy three-years old lady that reported to our clinic with FS affecting the maxilla. The objective of our study was to discuss the biological behavior of this tumour and treatment modalities. Clinical evaluation revealed a huge tumour involving the whole left maxilla. Radiographically the tumour involved both maxillary sinuses and the nose. Histologically,the Haematoxylin and Eosin (H&E) stained tissue sections revealed apoorly differentiated FS from the soft tissue of the maxilla. Surgery, which would entail a wide resection of bones of the region including the floor of the orbit and nasal bones, was thought to be incompatible with life and instead the patient was referred for palliative radiotherapy. The biological behavior of this tumour (locally destructive, late metastasis) enables our patient to contain that huge and extensive lesion to such an extreme age. As FS may metastasize to the lungs, liver and bones, follow-up of the patient with chest x-rays or CTScan would have been very important following surgery. The prognostic factors for FS depend on clinical stage, histological grade of malignancy, tumour location, local recurrences and incomplete resection if surgery contemplated. Taking into account that our case was of a poorly differentiated grade, coupled with the fact that the tumour was located at inaccessible site, factors that pointed to a poor prognosis. These factors affected the survival of the patient with FS.Key words: Fibrosarcoma, Craniofacial, Biological behaviour, Management.